Low temperature recombination luminescence of Mg3Y2Ge3O12:Tb3+ - Rogulis, Uldis; Fedotovs, Andris; Berzins, Dzintars; Krieke, Guna; Skuja, Linards; Antuzevics, Andris (Elsevier B.V., 2024)
A study was conducted to examine the recombination processes in persistent phosphor Mg3Y2Ge3O12:Tb3+ garnet at low temperatures. Photoluminescence (PL), recombination luminescence (RL), electron paramagnetic resonance (EPR), and EPR detected by PL or RL were measured. In samples with low Tb3+ concentration, a broad PL and RL band around 400–450 nm and characteristic Tb3+ lines were observed. However, in samples with high Tb3+ concentration, only Tb3+ lines were present. Both the broad-band and the line components exhibit long-lasting tunneling luminescence with hyperbolic decay. After 263 nm UV irradiation signals of intrinsic electron (F-type) and hole (V-type) trapping centres were observed in the EPR spectra. Such signals were also observed in RL-detected EPR spectra, indicating that the broad RL band at low Tb3+ concentrations originates from tunneling recombination between these intrinsic traps. At high Tb3+ concentrations, the RL-EPR spectrum was not observed, suggesting that intrinsic electron and Tb-related hole trapping centres probably participate in the tunneling recombination. © 2024 The Authors --//-- This is an open-access article U. Rogulis, A. Fedotovs, Dz Berzins, G. Krieke, L. Skuja, A. Antuzevics, Low temperature recombination luminescence of Mg3Y2Ge3O12:Tb3+, Optical Materials: X, Volume 24, 2024, 100368, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2024.100368.
This research is funded by the Latvian Council of Science, project "Defect engineering of novel UV-C persistent phosphor materials," Project no. lzp-2021/1-0118. Institute of Solid State Physics, University of Latvia, as the Centre of Excellence, has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Afterglow; Electron paramagnetic resonance; Mg3Y2Ge3O12:Tb3+; Paramagnetic centres; Photoluminescence; Recombination mechanism